FORMATION OF MATHEMATICAL LITERACY OF PRIMARY SCHOOL STUDENTS THROUGH INTEGRATION (Web of Teachers: Inderscience Research, 2024)
This article describes the development of mathematical literacy of primary school students through extracurricular activities and their interests.